STUDENTS' PERCEPTIONS TOWARDS CODE MIXING BY ENGLISH TEACHERS IN THE TEACHING PROCESS AT MA MA'ARIF NU RIAU - Ramdani, Ananda Suraiya; Purwanti, Indah Tri; Eliwarti, Eliwarti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract : This research examines students' perceptions of code mixing used by English teachers at a high school MA MA'ARIF NU RIAU in Pekanbaru. The study aimed to understand how students view the function, motives, impact, and their attitudes toward code mixing in English classes. Using a quantitative design, data were gathered through questionnaires completed by 100 students. Results show that students perceive code mixing as highly beneficial in explaining differences between their native language and English, with a mean score of 4.64. In terms of motives, students agreed that code mixing enhanced understanding and reduce misunderstandings, with the highest mean score of (4.78). The impact of code mixing was also viewed positively, with a mean score of 4.64, which means that students agreed its effectiveness for learning English. Regarding attitudes, students responded positively, with a high mean score (4.39) for combining Indonesian and English. This indicated that they view code-mixed instruction as important for better comprehension. Overall, the findings suggest that students support code mixing as an effective and engaging method for English learning, although there are still some limitations.Key words: Student Perception, Code Mixing, English Teaching